90=(3x-5)+(2x)

Simple and best practice solution for 90=(3x-5)+(2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=(3x-5)+(2x) equation:


Simplifying
90 = (3x + -5) + (2x)

Reorder the terms:
90 = (-5 + 3x) + (2x)

Remove parenthesis around (-5 + 3x)
90 = -5 + 3x + (2x)

Combine like terms: 3x + (2x) = 5x
90 = -5 + 5x

Solving
90 = -5 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
90 + -5x = -5 + 5x + -5x

Combine like terms: 5x + -5x = 0
90 + -5x = -5 + 0
90 + -5x = -5

Add '-90' to each side of the equation.
90 + -90 + -5x = -5 + -90

Combine like terms: 90 + -90 = 0
0 + -5x = -5 + -90
-5x = -5 + -90

Combine like terms: -5 + -90 = -95
-5x = -95

Divide each side by '-5'.
x = 19

Simplifying
x = 19

See similar equations:

| 6x^2+7x-21=0 | | y=-5/7x-4 | | 123+180=180 | | -2ab-ab= | | (-92)+63= | | 5g+9=5 | | 5(c-2)=5b-3 | | 6-4=7X-9X-8 | | 5g+9=-5 | | -2r=-34 | | 1.2(x-5)=1.6(2x+5) | | (x+3)(x+3)=12*x | | (2m+3)(6m-2)= | | 10x+-9x= | | 3r^2-9r-17=2r^2-5-8r | | 44x+7=73 | | 123+45=180 | | -2(8+4h)= | | x=5.6+1.4y | | 123+70=180 | | 2g+5=-3 | | (-7n/12)(9n/14) | | 9-5x=6x | | (2y-3)/(y+3)=5/7 | | 2h+5=3 | | 5x+3=10x+-7 | | 123+75=180 | | (-55)-(-88)= | | 6(7+x)+5x=0 | | -(8-4h)= | | 6f-1=2 | | 4s^4-17s^2+4=0 |

Equations solver categories